Programa educativo de destrezas emocionales para el mejoramiento de la tolerancia al error en aprendizajes en estudiantes de ciencias sociales del quinto grado de secundaria Institución Educativa Colegio Nacional de Iquitos 2023 - Diaz Rios, Zaira Vanessa (2024)
The central purpose of this research is to evaluate the effect of an educational program focused on emotional skills on improving error tolerance in high school Social Sciences students at the Colegio Nacional de Iquitos during the year 2023. This addresses the research question: What is the effect of the emotional skills educational program on improving error tolerance in these students? An evaluative, longitudinal, field, and univariate design was adopted, with a population of 504 students and a sample of 71, divided into an experimental group of 35 students and a control group of 36. Data collection was carried out through a survey and a written performance test, validated by experts in the field. The findings reveal that the emotional skills educational program is effective in fostering greater error tolerance, enhancing the students' ability to manage predictable, complex, and intelligent errors. This indicates a significant advancement toward the development of a growth mindset and resilience, essential for effective learning. The consistency in variances and the normality of the data among the groups confirm the reliability of these results, highlighting the need to incorporate emotional skills into educational programs to equip students with the necessary skills for academic success and future challenges.